2012
DOI: 10.5152/akd.2012.218
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cardiac troponin-T and right ventricular Tei index in patients with hemodynamically stable pulmonary embolism: an observational study

Abstract: Objective: The role of increased troponin level in risk stratification of acute pulmonary embolism (PE) is well documented. However, relation between right ventricular (RV) myocardial performance (Tei) index and cardiac troponin-T (cTn-T) has not been well investigated. The purpose of this observational prospective study was to assess the relationship between the RV Tei index and cTn-T in patients with acute normotensive PE. Methods: Thirty-eight patients with acute PE diagnosed by computed spiral tomography p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
0
10
0
3
Order By: Relevance
“…Ne yazık ki, yapılan çalışmalarda sağ ventrikül (RV) dilatasyonu, hipokinezisi, artmış RV/sol ventrikül (LV) çap oranı, interventriküler septumda paradoksal hareket, trikuspit regurjitasyonu jet akım hızında artış, RV miyokardiyal ferformans indeksi gibi RVD ait farklı EKO bulguları kullanılmıştır 31,32,33,34 . Bu nedenle, EKO'da RVD'nin herkes tarafından kabul görmüş bir tanımı bulunmamaktadır.…”
Section: Sağ Ventrikül Fonksiyon Bozukluğunu Gösteren Belirteçler Görunclassified
See 1 more Smart Citation
“…Ne yazık ki, yapılan çalışmalarda sağ ventrikül (RV) dilatasyonu, hipokinezisi, artmış RV/sol ventrikül (LV) çap oranı, interventriküler septumda paradoksal hareket, trikuspit regurjitasyonu jet akım hızında artış, RV miyokardiyal ferformans indeksi gibi RVD ait farklı EKO bulguları kullanılmıştır 31,32,33,34 . Bu nedenle, EKO'da RVD'nin herkes tarafından kabul görmüş bir tanımı bulunmamaktadır.…”
Section: Sağ Ventrikül Fonksiyon Bozukluğunu Gösteren Belirteçler Görunclassified
“…Benzer şekilde, Jimenez ve ark'ları, yaptıkları metaanalizde, artmış cTn'lerin tüm nedenlere bağlı ölüm riskini 4.26 kat arttırdığını tespit ettiler 60 . Ayrıca, artmış cTn'lerle PAOI ve RVD arasında yakın bir ilişki olduğu gösterilmiştir 33,48,57 . Bu arada, cTnI ile T'nin etkinliği arasında fark gösterilememiştir.…”
Section: Kardiyak Troponinlerunclassified
“…While these two studies did not investigate the relationship between the RV Tei index and cTn-T, the current study examined this relationship. Positive correlations were found between cTn-T levels and RV Tei index (r=0.467, p<0.003) (10).…”
mentioning
confidence: 90%
“…In the article published in the current issue of the Anatolian Journal of Cardiology, Özsu et al (10) carried out a study on the relationship between the RV Tei index and cTn-T in patients with acute normotensive PE. The results of this study showed that RV Tei index has been frequently impaired in patients with acute PE and a significant recovery has been seen after the treatment.…”
mentioning
confidence: 99%
“…RV dysfunction, an important predictor of mortality in PE cases, may be determined by imaging methods (computed tomography [CT], echocardiography) or laboratory markers such as brain natriuretic peptide (BNP), N-terminal (NT)-pro BNP, cardiac troponin I (cTnI) or T (cTnT), and heart-type fatty acid-binding protein (h-FABP) [1,[7][8][9][10][11][12]. Creatinine kinase isoenzyme MB (CK-MB) is an important biomarker for detecting myocardial injury [13].…”
Section: Introductionmentioning
confidence: 99%